Ověřování stabilního provozu sítě nové generace měřením přenosových parametrů - Gregor, Lukáš (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2018)
Tato diplomová práce se zabývá měřením přenosových parametrů v přístupových sítích nové generace NGA. Cílem práce je sestavení a konfigurace testovací sítě a scénářů pro měření kvalitativních parametrů služeb a následné ověření stability přenosu. V teoretické části práce je popsáno obecné fungování sítí NGN, požadavky různých telekomunikačních služeb na kvalitativní parametry, metodika a doporučení pro měření přenosových parametrů v paketových sítích. Praktická část se zabývá konfigurací scénářů využívajících různé technologie a metodikou jejich testování. Měření bylo provedeno dle standardů IETF RFC 2544, IETF RFC 6349 testem ExacTCP a ITU-T Y.1564 testem EtherSAM. Pro měření byly využity měřící přístroje značky EXFO. Závěrem byly zhodnoceny výsledky měření scénářů dle uvedených doporučení a diskutována výhodnost využití těchto doporučení pro testování přístupových sítích NGA.

This thesis deals with the measurement of transmission parameters in the new generation access networks NGA. The aim of the thesis is to build and configure a test network and scenarios for the measurement of service quality parameters and then verify the transmission stability. The theoretical part describes general functioning of NGN networks, the requirements of different telecommunications services on quality parameters, methodology and recommendations for measuring transmission parameters in packet networks. The practical part deals with the configuration of scenarios using mainly MPLS technology and methodology of their testing. Measurements were performed according to recommendations IETF RFC 2544, IETF RFC 6349 with the ExacTCP test and ITU-T Y.1564 with the EtherSAM test. For measurements were used measuring instruments of EXFO brand. In conclusion, the measurement results according to the mentioned standards were evaluated and also the advantages of using the measurement according to the given standard in NGA access networks were discussed.
Verification of stable next generation networks via transmission parameters measurement
Keywords: IP; NGN; NGA; IETF RFC 2544; IETF RFC 6349; ITU-T Y.1564; MEF 23.1; kvalita služeb; QoS; triple play; latence; kolísání zpoždění; ztrátovost paketů; datová propustnost; IP; NGN; NGA; IETF RFC 2544; IETF RFC 6349; ITU-T Y.1564; MEF 23.1; quality of services; QoS; triple play; latency; jitter; packet loss; throughput